The Effect of Gender Diversity Top Management Team on Financial Performance of Banks in Indonesia - Zaenal Abidin; Mulyono Mulyono; R. Mahelan Prabantarikso; Edian Fahmy; Maria Yuli Yanti (Profesional Muda Cendekia Publishing, 2022)
This research aims to analyze the effect of gender diversity in Top Management Team on financial performance in commercial bank. The variable used for this research are gender diversity, Non Performing Loan (NPL), Net Interest Margin (NIM), Operational Efficiency Ratio (OER) and Return On Assets (ROA). Sampling determines by using purposive sampling method and sample in this research are 20 big banks only that have been listed in period 2018-2019. The analysis tools on this research are using Partial Least Square (PLS) with SmartPLS software. The result of this research shows that gender diversity has a significant negative effect on NPL, OER has a significant negative effect on ROA and other variables used in this research showed insignificant results.